Analysis Of Time Analysis Of Outstanding Medical Records To Improve The Quality Of Services At Dustira Hospital, Cimahi - Rosadi, Imam; Iqbal Purnama, Muhammad (Rifa'Institute, 2021)
The provision of medical record files depends on the availability of data, clear and accurate information. The speed of providing medical record files is one indicator of the quality of service in medical records. The purpose of the study was to determine the achievement of the Minimum Service Standards in the medical record unit in providing medical record files. The research method uses descriptive methods with a qualitative approach. Data collection was carried out for 5 days by recording the hours the patient registered in the outpatient registration section until the time the medical record file was found, located at the hospital. Dustira Cimahi. The result is as many as 2090 or 86,1% of medical record files with a provisioning time of ? 10 minutes, 340 or 13,9% of medical record files requiring a provisioning time of> 10 minutes. The conclusion is based on the provision of medical record files at the hospital. Dustira has met the minimum service standards with the set waiting time standards for outpatient services which is an average of <60 minutes, it is recommended to maintain and improve the quality of service.